The changing face of dentistry: nanotechnology - Kanaparthy R (Dove Medical Press, 2011)
Rosaiah Kanaparthy1, Aruna Kanaparthy2 1Department of Periodontics, 2Conservative Dentistry, Peoples Dental Academy, Bhopal, Madhya Pradesh, India Abstract: The human body comprises molecules; hence, the availability of molecular nanotechnology will permit dramatic progress to address medical problems and will use molecular knowledge to maintain and improve human health at the molecular scale. Nanomedicine could develop devices that are able to work inside the human body in order to identify the early presence of a disease, and to identify and quantify toxic molecules and tumor cells, for example. Nanodentistry will make possible the maintenance of comprehensive oral health by employing nanomaterials, including tissue engineering and, ultimately, dental nanorobots. This review is an attempt to highlight the possible applications of nanotechnology and the use of nanomaterials in dentistry. Keywords: nanotechnology, molecule, nanomedicine, nanodentistry, nanorobots